Digital Storytelling and Open, Networked Social Scholarship: A Narrative. Issue 1 (27th February 2019) - Barber, John F.
This essay responds to a challenge of the INKE 2018 gathering: To highlight activities that focus on the engagement and implementation of networked open social scholarship . One response to this challenge is to distribute scholarly communication as storytelling through multiple digital media channels. The author participated in an international, multidisciplinary fellowship focused on how to implement such an undertaking. This narrative describes the collaborative efforts, presentations, and practices that emerged from this open, social scholarship endeavor.